Matrix metallopropteinases in heart failure. - Tousoulis, D; Kampoli, A; Papageorgiou, N; Antoniades, C; Siasos, G; Latsios, G; Tsiamis, E; Stefanadis, C (2012)
Heart failure (HF) represents a complex multifactorial syndrome, characterized by crucial structural and functional abnormalities of the myocardium. Matrix metalloproteinases are associated with left ventricular dysfunction, adverse left ventricular remodelling and prognosis after acute myocardial infarction. There is a strong association between oxidative stress and MMPs in the pathophysiology of HF. As MMPs are strongly associated to the pathogenesis and pathophysiology of HF, several agents have been proposed as potential modulators of these molecules. Classical agents such as statins, angiotensin converting enzyme inhibitors (ACEIS) and beta-blockers and a variety of novel agents have been implicated in the pathogenesis and progression of heart failure via the matrix metalloproteinases pathway and consist of possible future therapeutic targets.